2016
DOI: 10.1194/jlr.p070144
|View full text |Cite
|
Sign up to set email alerts
|

Monoacylglycerol-enriched oil increases EPA/DHA delivery to circulatory system in humans with induced lipid malabsorption conditions

Abstract: This article is available online at http://www.jlr.org Dietary fats are not only a source of energy, but also of bioactive nutrients, which are essential in maintaining human health. Among the fats, some FAs are considered essential FAs (EFAs) because they are not de novo synthesized and humans lack the enzymes required for their biosynthesis. Dietary fat absorption involves two main steps: first, lipolysis of dietary triacylglycerol (TAG) by sn-1,3' specific gastric and (colipase-dependent) pancreatic lipases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
2
24
0
1
Order By: Relevance
“…Indeed, it has been suggested that this type of persistent malabsorption is not only due to insufficient enzymes but also due to incomplete intraluminal solubilization or reduced enterocyte uptake, or both [33,35,36]. Studies suggest that OM3 LC-PUFA may be anti-inflammatory and a benefit for cystic fibrosis patients, and that the MAG form exhibits a higher degree of efficient absorption than the TAG form [20][21][22][23]28,33,35,36].…”
Section: Eementioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, it has been suggested that this type of persistent malabsorption is not only due to insufficient enzymes but also due to incomplete intraluminal solubilization or reduced enterocyte uptake, or both [33,35,36]. Studies suggest that OM3 LC-PUFA may be anti-inflammatory and a benefit for cystic fibrosis patients, and that the MAG form exhibits a higher degree of efficient absorption than the TAG form [20][21][22][23]28,33,35,36].…”
Section: Eementioning
confidence: 99%
“…Interestingly, OM3 was shown to be an effective substrate to MGAT enzyme and could be used as a pre-digested fat [37,38] with potentially improved bioavailability compared to ethyl ester or TAG. This lipase-independent MAG carrier may offer a clinical advantage to patients struggling with fat malabsorption/maldigestion problems, for instance, patients with cystic fibrosis [21,[37][38][39].…”
Section: Eementioning
confidence: 99%
See 3 more Smart Citations